Clinical and prognostic evaluation of familial hypertrophic cardiomyopathy in two South African families with different cardiac beta myosin heavy chain gene mutations. - Posen, B. M. (1995)
BACKGROUND--Familial hypertrophic cardiomyopathy is the most common inherited cardiac disorder, with sudden cardiac death at a young age the most frequent cause of death in affected individuals. Some cases of familial hypertrophic cardiomyopathy are caused by missense mutations of the beta myosin heavy chain (beta MHC) gene on chromosome 14 and at least 17 such mutations have been described. Recent reports suggest that a correlation exists between a specific beta MHC gene mutation and prognosis in familial hypertrophic cardiomyopathy. This premise is currently being used as a basis to provide counselling for affected families. This mutation/prognosis association, however, has not been widely assessed as yet. The clinical and prognostic features of two South African families of mixed racial descent, in which different beta MHC gene mutations were segregating, were studied to evaluate this correlation. The results were compared with those of previously published reports of European families carrying the same mutations. METHODS--The beta MHC gene missense mutations in two affected families were identified by single strand conformation polymorphism analysis and sequencing (pedigree 106: Arg403Trp; pedigree 108: Arg249Gln). All family members were subjected to genotypic analysis using polymerase chain reaction amplification and restriction enzyme based mutation detection techniques. Clinical, electrocardiographic, and echocardiographic studies were performed on genotypically affected individuals in these two kindreds. RESULTS--The number of individuals identified in pedigree 106 with the Arg403Trp mutation was 32.10 individuals bore the Arg249Gln mutation in pedigree 108. The penetrance rate in adults (equal to or greater than 16 years), using the strict echocardiographic criterion of maximum left ventricular wall thickness > or = 13 mm, was 25% for pedigree 106 and 33% for pedigree 108. Familial hypertrophic cardiomyopathy compatible electrocardiographic and echocardiographic abnormalities were seen in 60% of genotypically positive individuals aged > or = 16 years in pedigree 106 and 80% in pedigree 108. The prognosis was uniformly benign in the two families. For pedigree 106 this corresponded to a report of no early sudden cardiac deaths in a French family with the Arg403Trp mutation. For pedigree 108 the absence of such deaths was in apparent contrast to the four cases reported in 24 genotypically affected individuals in a study of a kindred of European ancestry bearing the Arg249Gln mutation. CONCLUSION--This study of a large South African kindred confirmed the benign nature of the Arg403Trp mutation suggested in a previous report. The number and the relatively young age of affected individuals in a second South African family must be considered when comparing the absence of familial hypertrophic cardiomyopathy associated deaths with the intermediate survival reported for the Arg249Gln mutation in a European family. This investigation lends support to current evidence relating specific beta MHC gene mutations to prognosis, which may be used as a basis to provide counselling for affected families.